2011
DOI: 10.3109/10826084.2011.618963
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Among Young Men Who Have Sex With Men

Abstract: This study reveals associations between alcohol use and demographic variables, as well as the relation between alcohol use and sexual activity, using episodic data. Data were obtained during summer and fall 2008 from a sample of 558 gay, bisexual, and other young men who have sex with men (YMSM), ages of 13-29 years in New York City. Recruitment strategies targeted potential participants at gay-related venues and public spaces often frequented by YMSM. Alcohol use varied by race/ethnicity, with White YMSM co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…Prior research has shown that Black MSM may underreport drug use compared to other racial/ethnic groups (White et al, 2014). Finally, we recognize that substance may emerge earlier than age 18 among YMSM and that for a subset of the men in this study these patterns of substance use, including alcohol use, may have been developing for several years prior to the first assessment of the cohort study (Pollock et al, 2012). Finally, data for the present analysis come from the TLFB, which is an interviewer-administered assessment and therefore only conducted during on-site interviews.…”
Section: Discussionmentioning
confidence: 89%
“…Prior research has shown that Black MSM may underreport drug use compared to other racial/ethnic groups (White et al, 2014). Finally, we recognize that substance may emerge earlier than age 18 among YMSM and that for a subset of the men in this study these patterns of substance use, including alcohol use, may have been developing for several years prior to the first assessment of the cohort study (Pollock et al, 2012). Finally, data for the present analysis come from the TLFB, which is an interviewer-administered assessment and therefore only conducted during on-site interviews.…”
Section: Discussionmentioning
confidence: 89%
“…Global association studies typically suggest a positive association between aggregate substance use and sexual risk behaviors in the general population (Leigh and Stall, 1993) as well as among GBMSM, with positive associations found between condomless anal sex (CAS) and frequent alcohol use (Morin et al, 2005; Tawk et al, 2004), heavy alcohol use (Colfax et al, 2004; Koblin et al, 2003; Woody et al, 1999), and any use of marijuana (Koblin et al, 2003) or club drugs, including cocaine, MDMA/ecstasy, methamphetamine, GHB, and ketamine (Colfax et al, 2005; Drumright et al, 2006b; Klitzman et al, 2002; Koblin et al, 2003; Purcell et al, 2001, 2005; Rusch et al, 2004; Woody et al, 1999). In addition to increased risk of CAS, recent studies continue to support associations between global alcohol and drug use and an increased number of sexual partners (Greenwood et al, 2001; Klitzman et al, 2002; Pollock et al, 2012). For example, Klitzman and colleagues found that, compared to low frequency MDMA users, higher frequency MDMA users had more sex partners and more “one night stands” (Klitzman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown high rates of alcohol use and abuse among men who have sex with men (MSM; Stall et al, 2001; Woolf and Maisto, 2009; Reisner et al, 2010; Pollock et al, 2012). Factors associated with problematic alcohol use among MSM include depression (Reisner et al, 2010), lower socio-economic status, history of incarceration, frequenting gay bars (Wong et al, 2008), HIV positive status (Deiss et al, 2013) and non-gay sexual identity (Agronick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%